Santam : crop insurance and climate change - Rosenthal, Jean; Elias, Jaan; Cort, Todd; Hamann, Ralph ([London] : SAGE, 2016)
Santam, the leading short-term insurer in South Africa, was pursuing a strategy to build climate change resilience in South Africa. In particular, the company was taking a look at its crop insurance business. Santam faced considerable challenges in this area as growers in much of Africa had not been interested in insurance in the past. How could the company make crop insurance more feasible? And how could the company share its expertise in risk management and mitigation to benefit Africa in the face of climate change?
Originally Published in: Rosenthal, J., Elias, J., Cort, T., & Hamann, R. (2015). Santam - Crop Insurance and Climate Change. 102-15. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://nexus.som.yale.edu/santam/.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Santam; Insurance -- South Africa -- Case studies; Crops and climate -- South Africa -- Case studies; Strategic planning -- Case studies; Business planning -- Case studies; Marketing -- Case studies